Confounding, Mediation, or Independent Effect? Childhood Psychological Abuse, Mental Health, Mood/Psychological State, COPD, and Migraine - Sheikh, Mashhood Ahmed (Journal of interpersonal violence, 2021)
In some settings, it may be difficult to differentiate between a confounder and a mediator. For instance, the observed association of self-reported childhood psychological abuse (CPA) with onset of chronic obstructive pulmonary disease (COPD) and migraine may be confounded by current mood/psychological state (e.g., the subjective evaluation of one’s own affective state), as well as mediated by an individual’s psychopathological symptoms. In this study, we propose the “independence hypothesis,” which could prove meaningful to explore in data that lack prospective or objective indices of CPA. We used cross-sectional data from wave VI (2007-2008) of the Tromsø Study, Norway (N = 12,981). The associations between CPA and COPD and migraine were assessed with Poisson regression models. CPA was associated with a 46% increased risk of COPD (relative risk [RR] = 1.46, 95% confidence interval [CI]: [1.02, 1.90]) and a 28% increased risk of migraine in adulthood (RR = 1.28, 95% CI: [1.04, 1.53]), independent of age, sex, parental history of psychiatric problems/asthma/dementia, smoking, respondent’s mood/psychological state, and mental health. These findings suggest that the association between retrospectively reported CPA and COPD and migraine is not driven entirely by respondent’s mood/psychological state and mental health. Assessing the independent effect of self-reported CPA on COPD and migraine in retrospective studies may prove more meaningful than exploring the mediating role of mental health. Here, we provide the analytical rationale for assessing the independent effect in settings where it is difficult to differentiate between a confounder and a mediator. Moreover, we provide a theoretical rationale for assessing the independent effect of retrospectively reported childhood adversity on health and well-being.